2010
DOI: 10.1134/s0006297910030144
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability and functional analysis of L-asparaginase from Pyrococcus furiosus

Abstract: We report studies on an L-asparaginase from Pyrococcus furiosus, cloned and expressed in Escherichia coli and purified to homogeneity. Protein stability and enzyme kinetic parameters were determined. The enzyme was found to be thermostable, natively dimeric, and glutaminase-free, with optimum activity at pH 9.0. It showed a K(m) of 12 mM and a substrate inhibition profile above 20 mM L-asparagine. Urea could not induce unfolding and enzyme inactivation; however, with guanidine hydrochloride (GdnCl) a two-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 37 publications
3
59
0
9
Order By: Relevance
“…The medical utilization of LAse from the reported sources suffer the limitations of eliciting immunological responses leading to hypersensitivity in the long-term usage, allergic reactions, anaphylaxis and instance of spontaneous resistance of the tumor cells [17] . So the present investigation was under taken with an aim and objective to search for a novel bacterium from an ecologically unexplored and extreme habitat for the production of cost effective, eco-friendly, thermostable and a potent LAse with new antigenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…The medical utilization of LAse from the reported sources suffer the limitations of eliciting immunological responses leading to hypersensitivity in the long-term usage, allergic reactions, anaphylaxis and instance of spontaneous resistance of the tumor cells [17] . So the present investigation was under taken with an aim and objective to search for a novel bacterium from an ecologically unexplored and extreme habitat for the production of cost effective, eco-friendly, thermostable and a potent LAse with new antigenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…In a study the Lasparaginase producing Streptomyces gulbargensis was subjected to mutagenesis by UV light and the mutant strains showed a higher yield in asparaginase production. Similarly Prema et al [19] reported 0.6 fold increase in L-asparaginase activity by the UV treated mutant strain of Pseudomonas fluorescens as compared to its wild strain. [19] it was observed that EMS mutated strains of Pseudomonas fluorescens showed increased L-asparaginase activity compared to its wild strains.…”
Section: Choice Of Mutagenmentioning
confidence: 99%
“…Similarly Prema et al [19] reported 0.6 fold increase in L-asparaginase activity by the UV treated mutant strain of Pseudomonas fluorescens as compared to its wild strain. [19] it was observed that EMS mutated strains of Pseudomonas fluorescens showed increased L-asparaginase activity compared to its wild strains. Ethidium Bromide is one of the intercalating mutagens that cause frameshift mutation.…”
Section: Choice Of Mutagenmentioning
confidence: 99%
See 2 more Smart Citations